Innovation in project management: Voices of researchers - Geraldi, Joana; Turner, J. Rodney; Maylor, Harvey; Hobday, Mike; Brady, Tim (Elsevier, 2009)
This paper reports and reflects on the discussions about the nature of the discipline of project management that took place during the 8th conference of the International Research Network of Organizing by Projects (IRNOP VIII), held in Brighton in September 2007. The discussions started with the provocative motion "This house believes that we no longer need the discipline of project management". The arguments are organised in the following areas: the use of the traditional body of knowledge by practitioners and by academics; the use of project management as a knowledge field by practitioners and by academics. The discussions indicate that project management research is in a fruitful moment of revolution of paradigms. We wish that the new paradigm accepts the plurality of research in projects and we need discussions supporting and also refusing the "motion", and by this means, proposing answers, rather than the answer, to the future of "the project management discipline".
Keywords: project management; innovation